Implementing EMI in Chinese music classes: Students’ perceived benefits and challenges - Su, Pengcheng; Kong, Jiayin (Frontiers in Psychology, 2023)
Recognizing the opportunities and problems of using English as a medium of instruction (EMI) enables teachers, students, and educational administrators to capitalize on the opportunities and mitigate the problems. Considering this, many researchers worldwide have explored the opportunities and problems of EMI courses. Yet, the advantages and disadvantages of implementing EMI in Chinese academic contexts have rarely been investigated. To fill this gap, the present research evaluated the benefits and challenges of implementing EMI in Chinese music classes. To accomplish this, a researcher-made scale was distributed among 74 Chinese music students. The thematic analysis of participants’ responses revealed that using English as a means of teaching and learning benefited Chinese music students in some ways. However, as the results of the thematic analysis indicated, Chinese music students experienced some serious challenges in EMI courses because of their limited English literacy. Finally, the limitations, pedagogical implications, and future research directions are thoroughly explained.